EVOLUSI RADIO REPUBLIK INDONESIA (RRI) SEBAGAI SITUS MEDIA INFORMASI TERTUA DAN EKSISTENSINYA DI MASA MODERN - Winda Kustiawan; Alphy Shahri Maulana; Arif Indra Hasan Harahap; Mahadir Muhammad; Zulhafiz Zulhafiz (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the evolution of Radio Republik Indonesia (RRI) as the oldest information media site and its existence in modern times. This study uses a descriptive qualitative method with the type of field research (field research). Furthermore, in data analysis techniques, researchers use the Miles and Huberman model, namely researchers present data, sort it, then make presentations and conclusions. In the technique of collecting data, the researcher made direct observations and conducted interviews. The results of this study indicate that the existence of RRI in modern times as the oldest information media site still goes with the flow and has enthusiasts even though the number is not much, therefore RRI is still in production as an information broadcast indicating that RRI as the oldest information site still has an existence in modern times. This is assessed based on the presence of RRI enthusiasts.